Anthropocentrism and anthropomorphism towards computers: definitions, predictors, and relationships with computer attitudes - Raffray, Benoit Joseph Marcel (My University, 1997)
The paper set out to define anthropocentrism and anthropomorphism with respect to computers as well as creating valid and reliable scales to measure these constructs. It also explored these constructs' relationship with attitudes towards computers and began to explore possible predictors of anthropocentrism and anthropomorphism. Anthropocentrism with respect to computers was defined as a motive or value in which people perceive humanity to be the most significant of all entities and in which computers are seen as valuable to the extent that they are able to maintain or enhance the quality of life of humans or provide benefits to them. Anthropomorphism with respect to computers was defined as the extent to which people believe that computers have the same capabilities and characteristics that humans have. As hypothesised. anthropocentrism. anthropomorphism and attitudes towards computers were found to be negatively related but distinct constructs. Anthropocentrism was found to be positively related to attitudes towards computers and anthropomorphism was inversely related to attitudes towards computers. Exploratory studies found that predictors of anthropocentrism included gender. and predictors of anthropomorphism included gender. culture. and experience with computers.
Thesis (M.A.)--University of the Witwatersrand, Arts Faculty (Industrial Psychology), 1997
Keywords: Computers -- Psychological aspects; Human-computer interaction -- Psychological aspects; Anthropomorphism; Attitude (Psychology)